Dampak Kualitas Kehidupan Kerja dan Motivasi Kerja pada Employee Engagement - Fatmasari Endayani; Saman Saman (Jurnal Bisnis dan Manajemen, 2021)
This study aims to analyze the level of Employee Engagement in education personnel at Merdeka University Malang and another factors related to quality of work life and work motivation. This research was followed by 60 employees of Education Staff of Merdeka University Malang. Explanatory research using a quantitative approach was applied in this research. This study explores the phenomenon of organizations that are increasingly responsive to employee needs. This phenomenon happen so that the company does not lose its best people. Yet the issue of stealing employees is still frequently heard. Organizations are competing to retain employees by paying attention to the quality of work life of their employees and providing encouragement in the form of motivation to retain employees. Based on the simultaneous test results, it can be concluded that there is a significant influence between the quality of work life and work motivation on employee engagement. However, in partial testing, it can be concluded that there is no significant effect between the Quality of Work Life variable and the Employee Engagement variable.